2017
DOI: 10.1002/joe.21827
|View full text |Cite
|
Sign up to set email alerts
|

Network relationships and internationalization in Tunisian high‐tech SMEs

Abstract: How do the dynamics of social and business networks influence the internationalization of small to medium‐size high‐tech businesses? This question is particularly relevant for small and medium‐size enterprises (SMEs) in developing economies, which frequently do not have access to the resources required for successful international expansion. A qualitative study of three Tunisian firms explores the role played by networks in the internationalization of high‐tech SMEs. The results show that personal, local, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Social networks contribute to the existence of business networks and, currently, an internationalisation strategy must include the use of social media (Paniagua et al, 2016). Through social media companies can accelerate internationalisation (Maltby, 2012) and reduce the costs inherent to a global presence (Maltby, 2012;Mejri & Ramadan, 2017). These two findings are relevant to the establishment of two propositions:…”
Section: Social Network In the Internationalization Processmentioning
confidence: 93%
See 2 more Smart Citations
“…Social networks contribute to the existence of business networks and, currently, an internationalisation strategy must include the use of social media (Paniagua et al, 2016). Through social media companies can accelerate internationalisation (Maltby, 2012) and reduce the costs inherent to a global presence (Maltby, 2012;Mejri & Ramadan, 2017). These two findings are relevant to the establishment of two propositions:…”
Section: Social Network In the Internationalization Processmentioning
confidence: 93%
“…Social networks provide the establishment and development of international relationships, contributing to increasing initial credibility, access to additional relationships and established channels, help firms in lowering costs and minimizing the risk of internationalisation (Zain & Ng, 2006), locate foreign individuals and organizations, interact with foreign customers, partners, and other stakeholders, demonstrate evidence of the value provided by their solutions (Arnone & Deprince, 2016), discover business opportunities (Chandra et al, 2009), decrease in time, increase in geographical scope (Batas & Liu, 2013), ease in the internationalisation process (Batas & Liu, 2013;Zain & Ng, 2006), reduction in transaction costs (Mejria & Ramadan, 2017;Zain & Ng, 2006), decrease in risks and uncertainties (Mejri & Ramadan, 2017).…”
Section: Social Network In the Internationalization Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In the international context, the findings of this study are consistent with those of similar studies previously conducted in Tunisia, Kazakhstan, Slovenia, Sweden, the US, Spain, India, Taiwan and Algeria. Mejri and Ramadan (2017) found that the ability to identify and exploit an international opportunity is a CSF for the internationalisation of Tunisian high-tech SMEs. In Slovenia, Ciszewska-Mlinaric and Mlinariè (2010) found that managerial attitudes towards internationalisation and internationalisation knowledge are significantly related to the level of SMEs' internationalisation.…”
Section: International Market Knowledge and Smes' Internationalisationmentioning
confidence: 99%
“…Companies operating in high-tech industries face rapid changes in technology, along with a need for market and customer knowledge, as they operate in a proactive industry with innovative dynamism [5]. They are knowledge-and technology-intensive and highly competitive [6,7]. Technology-based companies are also considered high-risk and high-return [1].…”
Section: High-tech Sector and Its Internationalization-theoretical Insights Of Its Importancementioning
confidence: 99%